Numerical Study to Assess the Structural Behavior of the Bajrakli Mosque (Western Kosovo) - Huseyin Bilgin; Faton Ramadani (Advances in Civil Engineering)
Cultural heritage is one of most significant concerns in modern societies carrying different social and historical values. Among the stock of cultural heritage, historical monuments are one of the greatest contributors to the values in many aspects. Due to several factors, such structures have gone through changes causing structural deficiencies. The aim of this study is to provide a clear insight of the cause and impacts of structural deficiencies through visual inspections and computational methods. As a representative model, Bajrakli Mosque located in western of Kosovo is selected as a case study. During visual inspections, some cracks are found along the structural elements of the mosque. A possible cause of the structural cracks may be the stress concentration through the regions of the structure. In order to provide a better understanding, two different loadings are considered to examine the structural behavior of the mosque. The first loading covers the analysis due to gravity loads, whereas the second one defines the dynamic loading due to ground shakings defined by the earthquake spectrum using finite element analysis in SAP2000. By means of these analyses, the performance of the building is examined. As a result, important data are obtained for identifying the critical regions of the structure. The maximum displacement of the structure is found to be 7.1 mm and 8.0 mm in combination of self-weight and earthquake load in X and Y direction, respectively. Moreover, the regions showing highest values of stress concentration are found through the small domes, through the openings of main dome and connections with arches, and around the openings of the walls.